Handbook of the international political economy of governance - Payne, Anthony, 1952-; Phillips, Nicola, 1971- (Cheltenham : Edward Elgar, 2014)
Since the 1990s many of the assumptions that anchored the study of governance in international political economy have been shaken loose. Reflecting on the intriguing and important processes of change that have occurred, and are occurring, the editors bring together the best research currently being undertaken in the field.
Keywords: International economic relations; Law and economics